Disposition of Aerosols of Isothiazolinone-Biocides: BIT, MIT and OIT - Seungmi Lee; Heui-Jin Park; Eunice B. Lee; Do Hyeon Lee; Dalwoong Choi; Kyung-Min Lim (Toxics, 2022)
Biocides are widely used in everyday life, and accordingly, human exposure to them is inevitable. Especially, the inhalational exposure of humans to biocides and resultant respiratory toxicity are gaining public interest due to the recent catastrophe associated with humidifier disinfectants. Aerosolized chemicals are subject to gravitational deposition and chemical degradation. Therefore, the characterization of the disposition of aerosols is essential to estimate the inhalational exposure to biocides. Here, we compared the disposition of aerosols of one of the commonly used biocide classes, isothiazolinone-based biocides, BIT, MIT, and OIT. An acrylic chamber (40 cm × 40 cm × 50 cm) was created to simulate the indoor environment, and a vacuum pump was used to create airflow (1 LPM). Biocides were sprayed from a vertical nebulizer placed on the ceiling of the chamber, and the distribution of particle sizes and volume was measured using the Optical Particle Sizer (OPS) 3330 device. During and after the aerosol spraying, airborne biocides and those deposited on the surface of the chamber were sampled to measure the deposition using LC-MS/MS. As a result, the broad particle size distribution was observed ranging from 0.3 to 8 μm during the nebulization. The inhalable particle faction (>2 μm) of the isothiazolinones was 32–67.9% in number but 1.2 to 6.4% in volume. Most of the aerosolized biocides were deposited on the chamber’s surface while only a minimal portion was airborne (<1%) after the nebulization. More importantly, significant amounts of MIT and OIT were degraded during aerosolization, resulting in poor total recovery compared to BIT (31%, 71% vs. 97% BIT). This result suggests that some isothiazolinones may become unstable during nebulization, affecting their disposition and human exposure significantly.